Virtuous Leadership Behaviors and their Role in Talent Management Practices: A Survey Study of the Opinions of a Sample of Employees at Al-Noor Private University - Saja Nazir Hamid Al-Sarraf (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This research investigates the relationship between virtuous leadership behaviors and talent management practices in business organizations, focusing on the strength and impact of these behaviors on talent management practices. The descriptive approach was used in the research, and a total of 150 questionnaires were distributed to a sample of working individuals represented by (faculty members) at Al-Noor Private University. The Likert scale (three-point) was used to answer the questionnaire paragraphs, and the statistical program represented by (Spss) was used to analyze the research data. The research showed a set of results, the most important of which is the existence of a strong positive relationship between virtuous leadership behaviors and talent management. The results also indicate that after self-control came the strongest association with talent management, followed by courage and humanity in third place, while after justice came in fourth place with a strong association with talent management Finally, after rationality, it came in last place with the strength of the association with talent management. The research presented a number of proposals, including the formation of a set of precise and direct criteria for selecting academic leaders based on capabilities and intelligence to master extensive knowledge, science and learning, with the necessity and guarantee of a pledge to remain in his position or leadership position for a specific period of time. The formation of a set of precise and direct criteria for selecting academic leaders based on capabilities and intelligence to master extensive knowledge, science and learning, with the necessity and guarantee of a pledge to remain in his position or leadership position for a specific period of time.